FORMULASI MINUMAN BST (BREAKFAST STARCHY TUBER) BERPREBIOTIK DARI PATI RESISTEN TIPE II (RS2) KENTANG DAN UBI JALAR - Nurma Handayani; Jay Jayus; Herlina Herlina (Faculty of Agricultural Technology, University of Jember, 2013)
Potato and sweet potato starch were formulated to be a product of BST exhibiting prebiotic activities. The BST were developed under different rasio of potato and sweet potato starch (A1 = 25:75; A2 = 50:50; A3 =75:25). The BST dough were mixed and prepared under different temperature of mixing (B1 = 60 °C; B2 = 70 oC and B3= 80 oC). Based on the overall sensory evaluation, the best formula was of potato and sweet potato starch 75:25. However, higher values of prebiotic index and short chain fatty acid content were observed from the formula of potato and sweet potato starch of 25:75, compare to that of the rasio 75:25. The possible reason of this was that the sweet potato contain higher resistant starch. Keywords: starch, prebiotic, retention RS, prebiotic index, SCFA